Imagining religious communities transnational Hindus and their narrative performances - Saunders, Jennifer B. (Oxford University Press, 2019)
Satya's story: transnational social networks, narrative performances, and religion -- On the importance of Maalis: transnational communities, social imaginaries, and narrative performance -- New opportunities, the brain drain, and the Guptas -- Growing up Indian, becoming immigrants: interpreting immigration narratives -- One's own home is better than all other places: creating family and home as transmigrants -- Neither black nor white: moving to the Atlanta of the new south -- Sundarka: performing community and religion -- Toward a transnational Hinduism
Includes bibliographical references and index
Keywords: Soziales Netzwerk; Transnationale Politik; Religiöse Gemeinschaft; Diaspora -- Religion; Hindu; Globalisierung; Hinduismus; Hindu diaspora; Hindus / Migrations; Religious communities; Hindus / Religious life